Divide. A) (-1/5)÷(2/3) B)-2/3÷8/15 C)0.54÷(0.9)

Expert Answers
sciencesolve eNotes educator| Certified Educator

You need to divide two fractions, hence, you need to multiply the first fraction by the second reversed fraction such that:

`(-1/5)/(2/3) = (-1/5)*(3/2)`

You need to perform the multiplication of numerators and denominators, such that:

`(-1/5)/(2/3) = ((-1)*3)/(5*2)`

`(-1/5)/(2/3) = -3/10`

Since there are no duplicate factors to reduce, hence, performing the division `(-1/5)/(2/3)` yields `(-1/5)/(2/3) = -3/10.`